Evaluation of clinicians' knowledge of and attitudes to Ebola virus disease in Ebonyi State, Nigeria - Nnennaya Anthony Ajayi; Chiedozie Kingsley Ojide; Immanuel Anthony Ajayi; Kingsley Nnanna Ukwaja (Elsevier, 2019)
Introduction: Ebola virus disease (EVD) remains a global threat of international concern. Being at the frontline of medical care, clinicians are at high risk of infection. Inadequate knowledge of, or poor attitudes to, EVD among clinicians may lead to failure in the detection of and timely responses to EVD. We determined the knowledge of and attitudes to EVD among clinicians in Ebonyi State, Nigeria. Materials and methods: A descriptive, cross-sectional study was conducted among clinicians attending an EVD training programme in Ebonyi State, Nigeria. Knowledge and attitudes of the clinicians were evaluated using a structured questionnaire. Data were analysed using descriptive and inferential statistics. Results: Of 398 clinicians who participated in the study, 274 (68.8%) were 40 years and below and 312 (78.4%) were male. Most of the clinicians surveyed (298, 74.9%) had worked for 10 years or less, and 354 (88.9%) of them had not undergone any training on EVD. The overall mean knowledge score of EVD among respondents was 42.0 ± 3.9 (maximum 51), and 370 (93.0%) respondents had a good overall knowledge of EVD. Overall, 334 (83.9%) respondents had an appropriate attitude towards EVD control, while 64 (16.1%) had a poor attitude towards EVD control. Only male gender was an independent predictor of good knowledge of EVD (adjusted odds ratio 4.0, 95% confidence interval 1.8-9.0). Conclusions: There was generally a high level of knowledge and good attitude to EVD among the clinicians surveyed. The gaps in knowledge and attitudes identified should inform post-EVD control strategies and future training programmes.